Mandziuk I., Prisyazhna K. New class lubricants materials on demand “Green Tribology” - Мандзюк, І.А.; Присяжна, К.О. (Problems of Tribology, 2017)
The work is devoted to studying the structure and tribotechnical properties of modified natural fats are by grafting oligomer polyester (polyethylene terephthalate). Using computer modeling using empirical methods of calculation (the method of molecular mechanics) received a geometric image of the synthesized compounds that indicate the difference between the structure of PET-acylglycerol the structure of the initial fats by the geo-metrical shape of macromolecules and their placement in space. Measuring friction torque confirming the forma-tion of intermediate, stable film formed on the PET-acylglycerol surface friction. Tribological studies confirm that formulations designed lubricants based PET-acylglycerol containing additives target yield performance characteristics tribotechnical prevailing indices of industrial oils Litol-24 TsIATIM-201, Divinol Fett R2, R-113. On average, the critical load performance lubricants developed than for industrial oils rise to 45%, the value of the load welding tubs - 60%; wear rates are reduced by 54%, coefficients of friction - reduced 2 times. Keywords: “green technology”, natural fat, PET-acylglycerol, dipole moment, tribotechnical properties.